2014
DOI: 10.1152/physiolgenomics.00059.2014
|View full text |Cite
|
Sign up to set email alerts
|

In utero exposure to prepregnancy maternal obesity and postweaning high-fat diet impair regulators of mitochondrial dynamics in rat placenta and offspring

Abstract: The proportion of pregnant women who are obese at conception continues to rise. Compelling evidence suggests the intrauterine environment is an important determinant of offspring health. Maternal obesity and unhealthy diets are shown to promote metabolic programming in the offspring. Mitochondria are maternally inherited, and we have previously shown impaired mitochondrial function in rat offspring exposed to maternal obesity in utero. Mitochondrial health is maintained by mitochondrial dynamics, or the proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
50
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(55 citation statements)
references
References 55 publications
5
50
0
Order By: Relevance
“…Either maternal or paternal HFD in isolation has been shown to change the transcriptome of the developing placenta (5,8,46,75). Thus, we determined whether there were additive effects of combined paternal and maternal HFD on placental gene expression during gestation.…”
Section: Paternal and Maternal Hfd Alter Placental Gene Expressionmentioning
confidence: 99%
See 1 more Smart Citation
“…Either maternal or paternal HFD in isolation has been shown to change the transcriptome of the developing placenta (5,8,46,75). Thus, we determined whether there were additive effects of combined paternal and maternal HFD on placental gene expression during gestation.…”
Section: Paternal and Maternal Hfd Alter Placental Gene Expressionmentioning
confidence: 99%
“…As both in vivo-and in vitro-derived fetuses and placentas were reduced in size with combined paternal and maternal obesity, and since both pater-nal and maternity obesity alone alter placental gene expression (5,8,46,75), we established whether key imprinting, growth, nutrition, and mitochondrial specific gene regulation were further impaired when both parents were obese. We observed sex-specific effects on placental gene expression that were expected given the numerous reports of sex-specific phenotypes in offspring in models of maternal and paternal obesity (18,19,22,23,63,66,67).…”
Section: Alterations To Fetal Health From Combined Paternal and Matermentioning
confidence: 99%
“…In fact, it has been shown that, in both, rodents and humans, skeletal muscle from high-fat fed conditions show higher H 2 O 2 -mitochondrial production affecting the redox state of the cells but without changes in the mitochondrial respiratory function (Anderson et al, 2009). Further experiments performed in rats demonstrated that exposure to prepregnancy maternal obesity impairs the activity of factors involved in mitochondrial dynamics in the offspring (Borengasser et al, 2014).…”
Section: Metabolic Syndrome Fat Accumulation and Mitochondriamentioning
confidence: 99%
“…Recent animal-based studies have suggested the effect of maternal obesity and postweaning high-fat diet on the key regulators of mitochondrial fusion and fission. Maternal obesity detrimentally changes mitochondrial targets which in turn, contribute to mitochondrial dysfunction and increased risk of obesity [24]. Potential modifications in mitochondrial bioenergetics may arise due to specific mutations that occur in the mitochondrial DNA.…”
Section: Mitochondrial Alterations In Obesitymentioning
confidence: 99%